Review of Open and equitable scholarly communications: Creating a more inclusive future - Davis, Jennifer (Journal of New Librarianship, 2020)
Abstract: Review of Maron, N., Kennison, R., Bracke, P., Hall, N., Gilman, I., Malenfant, K., Roh, C., & Shorish, Y. (2019). Open and equitable scholarly communications: Creating a more inclusive future. Chicago: Association of College and Research Libraries.